2015
DOI: 10.1016/j.cbpa.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional dynamics of claudin expression in Japanese medaka (Oryzias latipes): Response to environmental salinity

Abstract: Salinity regulation of 13 claudin paralogs was investigated in osmoregulatory organs of euryhaline Japanese medaka. They were identified by blast-search in the medaka genome database based on representation in osmoregulatory organs of other teleosts. Our hypothesis was that, because of their sequence similarities to mammalian orthologs previously characterized as barrier- and ion-selective channel-forming proteins, these paralogs would respond to salinity according to expected modulation of osmoregulatory func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 63 publications
6
23
1
Order By: Relevance
“…The time-course experiment showed that cldn15b was not significant affected by SW before 24 h and 168 h while the inhibitory effect on the two aqps was apparent at the 6 h and 24 h mark but not significant at the 168 h time point. Thus, while the dynamics of regulation are not straightforward, the overall inhibitory effect of SW on cldn15b, aqp1a, and aqp8ab observed previously was confirmed [8,34].…”
Section: Transcript Levels and Response To Salinitysupporting
confidence: 75%
See 2 more Smart Citations
“…The time-course experiment showed that cldn15b was not significant affected by SW before 24 h and 168 h while the inhibitory effect on the two aqps was apparent at the 6 h and 24 h mark but not significant at the 168 h time point. Thus, while the dynamics of regulation are not straightforward, the overall inhibitory effect of SW on cldn15b, aqp1a, and aqp8ab observed previously was confirmed [8,34].…”
Section: Transcript Levels and Response To Salinitysupporting
confidence: 75%
“…Based on similarities to the mammalian CLDN15 shown in Figure 11, we hypothesized that the two medaka orthologs, cldn15a and cldn15b, may share functional properties in terms of forming cation and water pores and therefore may contribute to paracellular water absorption in SW medaka. In fishes (medaka [34]; salmon [31,32]; zebrafish [33]) and mammals [12], CLDN15 orthologs are expressed especially, but not exclusively, in the GI tract. In Atlantic salmon, SW acclimation was shown to induce elevated intestinal cldn15a mRNA expression [32], and a different study in the same species documented higher transepithelial resistance in SW than FW intestine measured ex vivo [48].…”
Section: Transcript Levels and Response To Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another candidate gene cldn10 encodes a component of tight junctions. Seawater transfer induced elevation of cldn10 expression in the gills of medaka (Bossus et al 2015). It is likely that differential expression of cldn10 can contribute to divergence in salinity tolerance between ecotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Tipsmark et al [81] indicated that claudin 15 could regulate paracellular Na þ movement in the intestines of Atlantic salmon (Salmo salar). In Japanese medaka (Oryzias latipes) intestine, the mRNA levels of claudin 15a were significantly higher than the claudin 15b mRNA level in response to a salinity change, leading to a claudin 15b net transport of sodium that was negligible [82]. Meanwhile, Kaplan [83] reported that Na þ , K þ -ATPase carries out the uptake of Na þ in most higher eukaryotes.…”
Section: General Summary: Optimal Dietary Protein Level Improve the Imentioning
confidence: 99%